2019
DOI: 10.1177/2397791419863596
|View full text |Cite
|
Sign up to set email alerts
|

Fully developed magnetohydrodynamics natural convection flow in a vertical micro-porous-channel with Hall effects

Abstract: An exact solution is presented for the steady hydromagnetic fully developed natural convection flow in a vertical microporous channel due to asymmetric heating. The governing momentum and energy equations are presented in dimensionless form and solved analytically using the method of undetermined coefficient. The effects of Hall current and suction/injection parameters on the primary and secondary velocity, volume flow rates, and skin frictions are discussed with the help of line graphs and tables. It is obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The set of Bessel ordinary differential equations (12) and (13) with the boundary condition (14) are solved for velocity and temperature in the Laplace domain as follows:…”
Section: Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The set of Bessel ordinary differential equations (12) and (13) with the boundary condition (14) are solved for velocity and temperature in the Laplace domain as follows:…”
Section: Solutionmentioning
confidence: 99%
“…Recently, Lawal and Jibril 11 studied unsteady MHD natural convection flow of heat generating/absorbing fluid near a vertical plate with ramped temperature and motion. Jha et al 12 considered the fully developed MHD natural convection flow in a vertical microchannel with the effect of transverse magnetic field in the presence of velocity slip and temperature jump at the annular microchannel. They concluded that increase in curvature radius leads to an increase in the mass flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that irrespective of the thermal surrounding situation of the microporous channels, higher values of suction/injection parameter improve shear stress at the boundary walls. In related work, Jha et al 37 investigated the impact of suction/injection on MHD flow in the existence of Hall current. Other notable works on this subject could be found in Krishna, 38 Jha and Aina, 39 and Singh et al 40 …”
Section: Introductionmentioning
confidence: 99%
“…It was noted that irrespective of the thermal surrounding situation of the microporous channels, higher values of suction/ injection parameter improve shear stress at the boundary walls. In related work, Jha et al 37 investigated the impact of suction/injection on MHD flow in the existence of Hall current. Other notable works on this subject could be found in Krishna, 38 Jha and Aina, 39 and Singh et al 40 The present work is focused on investigating the interplay of suction and injection on the transient hydromagnetic flow of Newtonian viscous fluid through a microchannel in the prevalence of ion slip with Hall current and IMF effects.…”
Section: Introductionmentioning
confidence: 99%
“…Hichem and Mahfoud 22 investigated the natural convection in a horizontal elliptical annulus containing a fluid saturated porous medium effect of aiding buoyancy for a low Rayleigh‐Darcy number. The MHD natural convection of nanofluid in a concentric annulus between a cold outer square cylinder and a heated inner circular was investigated by Sheikholeslami et al 23 Jha et al 24 considered the fully developed MHD natural convection flow in a vertical micro‐channel with the effect of a transverse magnetic field in the presence of velocity slip and temperature jump at the annular micro‐channel; they concluded that increase in curvature radius leads to an increase in the mass flow rate. In all the above mentioned works, flow formation is due to impulsive/accelerated motion of the cylinder.…”
Section: Introductionmentioning
confidence: 99%